Morphmetrical and Histological Changes in Domestic Chicken Kidneys in Response to Salinated Water - Mustafa Saddam Ghaj (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The high ratio of salt in the water of my country (Iraq) had bad effect on the products of the poultry industry, therefor were focusing in this study on the effect of salt on the kidney of birds Material and Method: were carried on Twenty domesticate chicken(Gallus gallus) and divided into two groups (control and stressed) ten birds for each, used for determinate the morphological and histological differences in the kidneys .For histological study, kidney samples were taken to prepared slid to check the structure tissue of kidney in both groups. Result: The mean weight of kidney in stressed was (5.31 ± 0.55) g. It was heavier than the kidney of control group which weighted (4.08±0.47) g. The same difference was recorded about the size of kidney; the length (5.38 ± 0.49 cm) and width (2.40±0.32 cm) of kidney in stressed group was higher than that of control group (length 4.33±0.41 cm) and width (2.00±0.31 cm). Also some histological changes in stressed group was differed than control.Conclusion: The moderate salt level in food or drinking water was a toxic for chickens. The structure and function of chickens’ kidney were less efficiently to eliminate (NaCl), therefore severe histological changes in kidney and others vital organs.